Pengaruh Standing Frame Exercise terhadap Denyut Nadi pada Anak Cerebral Palsy - Nada‘Ainul Mardliyah; Agus Widodo (Jurnal Health Sains, 2021)
Children with Cerebral Palsy (CP) have abnormalities in vital signs, one of which is an increase in pulse at rest. This increase in pulse rate is associated with an increase in the level of motor disability, which applies to children who cannot walk and is classified as level IV and V Gross Motor Function Classification System (GMFCS). However, the function of the autonomic nervous system in children with CP has not been explored in depth and sufficiently. The autonomic nervous system functions to maintain homeostasis and regulates various automatic functions of the body, including temperature, pulse, blood pressure, and digestive. Standing frame exercise functions to manage Orthostatic Hypotension (OH) and improve the function of the cardiovascular system. This research aims to knowing the effect of standing frame exercise on pulse in children with CP. This type of research is Quasy Experimental using Two Pre-Test and Post-Test with Control Group Design. A sample of 12 respondents was divided equally into two groups of conventional treatments (massages) with standing frame exercise and the control group conventional therapy only. Frequency 3 times a week. The measurement instrument uses a pulse oxymeter. Paired Sample t-Test statistical test results in the treatment group obtained p-value 0.006 and 0.044 in the control group. The conclusion is there is an influence of standing frame exercise on the pulse in children with CP.